An analysis of the conflicts between competition law and intellectual property law / Raihanah Shukri … [et al.] - Shukri, Raihanah; Muhamad Rodzi, Husna; Zulkifli, Natasha Aida; Mohd Pattali, Siti Aishah (2013)
Competition law is one of the newest enacted laws in Malaysia. Competition law is to enhance competition especially between businessmen to mark up their game and compete with each other. Indirectly, this will boost the economic growth of our country. With the enforcement of competition law, Malaysia may face the same problem as other countries, which is the conflict that will arise from competition law and the intellectual property rights. Competition law will prevent any anti-competitive agreements while the intellectual property law protect the right of the owner of the inventions and other creations and will eventually lead to monopoly. Therefore, there is a need to analyse these laws and the problems that may arise to reduce the problems. The title of this project paper is, "An Analysis of the Conflicts between Competition Law and Intellectual Property Law". There are four main objectives in this research which are to analyse the conflict that may arise due to the relationship between the competition law and intellectual property rights, to identify the effect on complication, to compare with the jurisdiction of other countries, in order to analyse the mechanism used in handling the conflict and propose guidelines to minimize the conflicts between these two laws. This research focuses on the competition law and intellectual property rights in Malaysia and some other countries such as the United Kingdom, the United States, and Europe. This research is a qualitative research and it will be doctrinal in nature.